2021
DOI: 10.3389/fcell.2021.632303
|View full text |Cite
|
Sign up to set email alerts
|

HOXA5 Participates in Brown Adipose Tissue and Epaxial Skeletal Muscle Patterning and in Brown Adipocyte Differentiation

Abstract: Brown adipose tissue (BAT) plays critical thermogenic, metabolic and endocrine roles in mammals, and aberrant BAT function is associated with metabolic disorders including obesity and diabetes. The major BAT depots are clustered at the neck and forelimb levels, and arise largely within the dermomyotome of somites, from a common progenitor with skeletal muscle. However, many aspects of BAT embryonic development are not well understood. Hoxa5 patterns other tissues at the cervical and brachial levels, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…It has also been shown that Hoxa5 counteracts stem cell traits through inhibiting Wnt signaling in colorectal cancer [ 24 ]. Meanwhile, previous studies also demonstrated that Hoxa5 is required for adipose tissue development [ 25 ] and is a positive regulator of adipogenesis both in humans and mice [ 26 , 27 , 28 ]. In 3T3-L1 preadipocyte, Hoxa5 influences adipogenesis by positive transcription regulation of the fatty-acid binding protein 4 (FABP4), which is the master adipogenesis regulator [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that Hoxa5 counteracts stem cell traits through inhibiting Wnt signaling in colorectal cancer [ 24 ]. Meanwhile, previous studies also demonstrated that Hoxa5 is required for adipose tissue development [ 25 ] and is a positive regulator of adipogenesis both in humans and mice [ 26 , 27 , 28 ]. In 3T3-L1 preadipocyte, Hoxa5 influences adipogenesis by positive transcription regulation of the fatty-acid binding protein 4 (FABP4), which is the master adipogenesis regulator [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Ewing sarcoma, bone-morphogenic protein 7, and homeobox A5 are critical regulators of brown adipogenesis in cultured cells, and its loss of function reduces BAT mass in mice. 54 , 55 , 56 , 57 These previous reports clearly indicate that the regulatory mechanisms of brown adipogenesis in cultured cells are closely related to BAT development in vivo . Therefore, MVA pathway–mediated regulation of brown adipocyte differentiation is thought to be important for BAT development in vivo .…”
Section: Discussionmentioning
confidence: 65%
“…In the skeletal system, Hoxa5 expression is in vertebral cartilage condensations, anterior rib condensations, and the sternal mesenchyme from E12.5 through E16.5 23,26‐29 . Hoxa5 expression has also been reported in brown adipose tissue from E14.5 to E18.5 28,30 . Within the lung, Hoxa5 is exclusively expressed in the mesenchyme, and not in the epithelium, during development 19 …”
Section: Introductionmentioning
confidence: 87%